2012
DOI: 10.1007/s00360-012-0725-0
|View full text |Cite
|
Sign up to set email alerts
|

Torpor as an emergency solution in Galago moholi: heterothermy is triggered by different constraints

Abstract: The expression of heterothermy in the African lesser bushbaby, Galago moholi, seems to be strikingly different to most other heterotherms: G. moholi uses its ability to enter torpor only rarely and torpor is only used by a small fraction of the population. The aim of this study was, therefore, to summarize the parameters of torpor use in G. moholi to conclude the general patterns and discuss them in comparison to other heterotherms to elucidate possible causes and constraints that underlie these differences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 38 publications
0
38
0
Order By: Relevance
“…This has significant effects on both sexes: it is disadvantageous for females to become heterothermic because they are either pregnant or nursing, both known to be impaired by heterothermy (Racey & Swift, ; Wilde, Knight & Racey, ), and males have to keep spermatogenesis functioning (Fietz et al ., ) and territories set up. The availability of high‐quality food (energy content of gum increases during winter), albeit in low quantities, as well as behavioural adaptations, presumably enable G. moholi to stay euthermic throughout the comparatively short cold, dry period and to focus on reproductive activities (Nowack et al ., 2013a). Clearly, heterothermy is not a routine seasonal adjustment for G. moholi , but used as a last emergency strategy only.…”
Section: Heterothermy Outside Madagascar – the Big Step Over The Oceanmentioning
confidence: 97%
See 1 more Smart Citation
“…This has significant effects on both sexes: it is disadvantageous for females to become heterothermic because they are either pregnant or nursing, both known to be impaired by heterothermy (Racey & Swift, ; Wilde, Knight & Racey, ), and males have to keep spermatogenesis functioning (Fietz et al ., ) and territories set up. The availability of high‐quality food (energy content of gum increases during winter), albeit in low quantities, as well as behavioural adaptations, presumably enable G. moholi to stay euthermic throughout the comparatively short cold, dry period and to focus on reproductive activities (Nowack et al ., 2013a). Clearly, heterothermy is not a routine seasonal adjustment for G. moholi , but used as a last emergency strategy only.…”
Section: Heterothermy Outside Madagascar – the Big Step Over The Oceanmentioning
confidence: 97%
“…In G. moholi , on the other hand, only a small fraction (about 25%) of the population becomes heterothermic at all, mostly subadult males, and only on singular occasions (once or a few times within continuous days), suggesting an exclusive triggering event or situation. It seems that G. moholi enter torpid states as an acute emergency response only that preclude other options (Nowack, Mzilikazi & Dausmann, 2013b). Heterothermic phases are always short (less than 24 h) and arousal from torpor is a two‐step process under natural conditions, analogous to Microcebus , with a passive phase first, and active heating initiated later.…”
Section: Heterothermy Outside Madagascar – the Big Step Over The Oceanmentioning
confidence: 99%
“…Most female galagos, on the other hand, spend a large portion of the year reproducing, that is, pregnant or lactating, remaining active year round. Thus, torpor would not only interfere with embryonic development and/or milk production, but would also prevent them from accumulating substantial fat stores, a precondition for hibernation . It is generally agreed that the use of torpor in galagos appears to be restricted to “emergency” situations.…”
Section: Lines Are Blurred: Expression Of Primate Heterothermy In Thementioning
confidence: 99%
“…The closely related mouse lemurs, which, such as dwarf lemurs, are members of the family Cheirogaleidae, are capable of torpor (Ortmann et al 1997; Schmid 2001), although torpor bouts in these animals are typically shorter than 24 h. The other primate clade to express torpor is the Lorisiformes. The Asian pygmy slow loris was most recently documented to demonstrate bouts of sustained metabolic suppression under semicaptive conditions (Ruf et al 2015), whereas anecdotal reports of torpor have also been reported for their sister lineage, the bushbabies, under extreme energetic demands (e.g., Nowack et al 2013). In the western regions of Madagascar, fat-tailed dwarf lemurs ( Cheirogaleus medius ) engage in hibernation for up to 7 months wherein body temperature approximates ambient temperature (Dausmann et al 2004, 2005, 2009).…”
Section: Introductionmentioning
confidence: 99%